2022
DOI: 10.3233/npm-210722
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound guided pulmonary recruitment during mechanical ventilation in neonates: A case series

Abstract: BACKGROUND: Recently, the first report of lung ultrasound (LUS) guided recruitment during open lung ventilation in neonates has been published. LUS guided recruitment can change the approach to open lung ventilation, which is currently performed without any measure of lung function/lung expansion in the neonatal population. METHODS: We included all the newborn infants that underwent a LUS-guided recruitment maneuver during mechanical ventilation as a rescue attempt for an extremely severe respiratory condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…All the LUS-guided recruitments, starting from a consolidation pattern (C-pattern) and showing signs of lung recruitability performed between January 2019 and August 2021 were included in this case-control study and constituted the Lung UltraSound Targeted Recruitment (LUSTR) group. The recruitable lung was determined by the development of the S-pattern during pressure augmentation; this was based on our previous report [ 7 ]. The S-pattern is characterized by the presence of vertical hyperechoic artifacts starting from the reopening bronchi, representing a sonographic sign of lung recruitability.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All the LUS-guided recruitments, starting from a consolidation pattern (C-pattern) and showing signs of lung recruitability performed between January 2019 and August 2021 were included in this case-control study and constituted the Lung UltraSound Targeted Recruitment (LUSTR) group. The recruitable lung was determined by the development of the S-pattern during pressure augmentation; this was based on our previous report [ 7 ]. The S-pattern is characterized by the presence of vertical hyperechoic artifacts starting from the reopening bronchi, representing a sonographic sign of lung recruitability.…”
Section: Methodsmentioning
confidence: 99%
“…As these linear artifacts resemble the sun rays crossing the clouds, they were named Sunray(S)-lines. The pattern is characterized by the appearance of at least one S-line per field [ 7 ]. LRMs were excluded from the study if no S-pattern was detected during the procedure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that LUS can be used to guide pulmonary recruitment maneuvers during mechanical ventilation in neonates ( 170 , 171 ). As the developed artifacts resemble sunrays crossing the clouds, the novel S-lines (“sunray lines”) described in the LUS-guided protocol may improve the efficacy and safety of mechanical ventilation strategies in neonates ( 170 ). In addition, computer-aided image analyses have been developed to interpret LUS findings.…”
Section: Other Applications Beyond Diagnosismentioning
confidence: 99%